Shorani sheep carcass characteristics at different ages in Elabassia Tagali, Nuba Mountains, South Kordofan State, Sudan - Elimam, Mohmed; Gibreel, Mohmed (Gezira Journal of Agricultural Science, 2013)
Shorani sheep carcass characteristics were studied at <1, 1 and 2 years old in Elabassia Tagali area in the Nuba Mountains, South Kordofan State, Sudan in November 2002. Nine animals (three for each age group) were bought from local markets, rested, watered, fasted overnight and then slaughtered according to Islamic rituals. Slaughter weight, empty body weight (EBW) and hot carcass weight significantly (P<0.05) increased with increasing slaughter age. Empty body weight was lower than live body weight. Dressing percentages on live body weight and empty body weight increased with slaughter weight and were higher on EBW. Body components significantly (P<0.05) increased with increasing slaughter age. The percentages of all body components on EBW increased with increasing slaughter age from<1 to 1 year old and decreased at 2 years old. The percentages of muscles and bones significantly (P<0.05) increased with increasing the slaughter weight from<1 to 1 year old and then decreased. Fat percentages significantly (P<0.05) increased with slaughter age. Muscle: bone ratio significantly (P<0.05) increased with slaughter age to 1 year old and decreased at 2 years old. Muscle: fat ratio significantly (P<0.05) decreased with slaughter age.    تمت دراسة صفات ذبيحة أغنام الشوراني بأعمار أقل من عام ، عام وعامين في منطقة العباسية تقلي قي جبال النوبة في ولاية جنوب كردفان في  السودان في نوفمبر 2002م. أشتريت 9 حيوانات (3 في كل مجموعة عمرية) من الأسواق المحلية ، واريحت وسقيت ماء وصومت ليلا ثم ذبحت بالطريقة الإسلامية. زاد وزن الذبح والوزن الفارغ ووزن الذبيحة الساخنة معنويا بزيادة عمر الذبيح. وكان الوزن الفارغ أقل من الوزن الحي للحيوانات. زادت نسب التصافي على أساس الوزن الحي والوزن الفارغ بزيادة عمر الذبيح وكانت أعلى على أساس الوزن الفارغ. زادت أوزان مكونات الجسم الثانوية بزيادة عمر الذبيح. وزادت النسب المئوية لكل مكونات الجسم الثانوية على أساس الوزن الفارغ بزيادة عمر الذبيح من أقل من عمر عام إلى عمر عام وانخفضت بعمر عامين. زادت النسب المئوية للعضلات والعظام معنويا بزيادة عمر الذبيح من أقل من عمر عام إلى عمر عام ثم انخفضت. زادت النسب المئوية للشحم معنويا بزيادة عمر الذبيح. زادت العضلات : العظام معنويا بزيادة عمر الذبيح إلى عمر عام ثم انخفضت بعمر عامين. وزادت العضلات : الشحم معنويا بزيادة عمر الذبيح.